THE DEVELOPMENT OF AGROINDUSTRY AND TRANSPORTATIONAL NETWORK IN THE CENTRAL JAVA DURING DUTCH COLONIZATION (History Department, Semarang State University and Historian Society of Indonesia, 2014)
The Java Land has been developed into a big plantation area, especially a sugar cane and coffee plantation. Those plantation was carried out since the seventeenth century by VOC , and then it is developed rapidly in nineteenth century, especially in the cultivation system period. The development of plantation company needs supporting vehicles and facilities. As a result of this, there are a development of land transportation, especially a train since the middle of the nineteenth century and the water transportation includes a big ships which enliven some harbours in Java, such as Semarang, Jakarta, Cirebon and Surabaya. Keywords: agroindustry, transportation network, Dutch colonization Tanah Jawa pernah berkembang menjadi wilayah perkebunan yang besar, terutama perkebunan tebu dan kopi. Usaha perkebunan itu mulai dilakukan sejak abad ke-17 oleh VOC, dan berkembang pesat pada abad ke-19, terutama sejak masa Tanam Paksa. Perkembangan perusahaan perkebunan memerlukan sarana pendukung transportasi. Akibatnya berkembanglah transportasi darat, terutama kereta api sejak pertengahan abad ke -19 dan transportasi laut berupa kapal-kapal besar yang meramaikan sejumlah pelabuhan laut di Jawa, seperti Semarang, Jakarta, Cirebon, dan Surabaya. Kata kunci: agroindustry, jaringan transportasi, kolonial Belanda